2017
DOI: 10.1530/rep-17-0367
|View full text |Cite
|
Sign up to set email alerts
|

Genes of cellular components of morphogenesis in porcine oocytes before and after IVM

Abstract: Proper oocyte maturation in mammals produces an oocyte capable of monospermic fertilization and embryo preimplantation. The cumulus-oocyte complexes (COCs), surrounding an oocyte, play a significant role in oocyte maturation. During this process, when the COCs undergo cumulus expansion wherein tightly compact cumulus cells (CCs) form a dispersed structure, permanent biochemical and molecular modifications occur in the maturing oocytes, indicating that the gene expression between immature and mature oocytes dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 64 publications
3
13
0
1
Order By: Relevance
“…These nuclear alterations, contributing to organelles reorganization in mammalian oocytes, both in vivo and in vitro, still need further investigation. As we showed previously [ 8 , 9 , 10 , 11 , 23 ], transcriptomic profile of gene expression differs significantly in porcine oocytes before and after IVM. Thus, to improve the quantity of mature and fertilizable oocytes, as well as IVF outcome, finding new molecular markers of maturation capability is highly recommended [ 24 , 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These nuclear alterations, contributing to organelles reorganization in mammalian oocytes, both in vivo and in vitro, still need further investigation. As we showed previously [ 8 , 9 , 10 , 11 , 23 ], transcriptomic profile of gene expression differs significantly in porcine oocytes before and after IVM. Thus, to improve the quantity of mature and fertilizable oocytes, as well as IVF outcome, finding new molecular markers of maturation capability is highly recommended [ 24 , 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 63%
“…It was well recognized in several species of mammals that only properly structuralized mature oocyte (MII) may be successfully fertilized by spermatozoon, and each stage of early folliculogenesis and oogenesis influences further embryo growth and development [ 5 , 6 , 7 ]. Our previous experiments indicated an increased expression of genes involved in “Bone development”, “Cellular components of morphogenesis”, “BMP signaling pathway”, and “Cell migration”, which were intensively regulated during in vitro maturation of porcine oocytes (IVM) [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies revealed large set of genes influencing maturation capability of porcine oocytes. We know that the differences in gene expression before and after in vitro maturation (IVM) reflect changes in oocytes and its susceptibility for future fertilization [3][4][5]. This observation can result in development of molecular diagnostic of female gametes before proceeding to IVM.…”
Section: Introductionmentioning
confidence: 99%
“…In porcine oocytes, the vast majority of genes recruited in morphogenesis can affect cell maturation as compared to mature oocytes. This means, that during morphogenesis, the process of oocyte maturation and developmental capacity are regulated by cellular modifications [20].…”
Section: Cytoplasmic Maturation Of Oocytesmentioning
confidence: 99%